Incur Debt to Adapt - Emmanuel Pannier; Phan Thị Kim Tâm (Revue Internationale des Études du Développement)
Drawing on an ethnographic study of housing adaptations following a historic flood in Vietnam's northern uplands, this paper examines the role of social networks in resilience. Numerous studies limit the analysis to formal groups and neglect the exploration of the web of personal relationships. Furthermore, the comparative role of social networks relative to, but also in combination with, other channels of resource circulation is seldom investigated. This paper documents and compares the various channels through which resources flow, examines their interactions, and characterizes the patterns of circulation. While state and market resources are crucial, they alone are insufficient. Social networks and indebtedness emerge as pivotal components of resilience to environmental hazards. However, they do not ensure long-term recovery for all individuals, as they may lead to over-indebtedness and dependency. Moreover, the uneven distribution of social capital contributes to disparities in adaptive capacity.